Landasan Berfikir Kesejahteraan Jiwa: Psikologi dan Tasawuf - Nurjamilah, Siti; Siti Nurjamilah; Rosid Bahar; Salman Alfarisi (Program Studi Tasawuf dan Psikoterapi, 2024)
Mental well-being is a topic that attracts attention from various disciplines, including psychology and Sufism. This research aims to explore the theoretical basis of mental well-being from the perspective of psychology and Sufism. This research is conducted in a descriptive qualitative manner using a literature approach. Data will be collected from various literature sources such as books, journal articles, and other academic works related to psychology and Sufism in the context of mental well-being. In the context of psychology, various theories such as self-determination theory, hedonic and eudaimonic well-being, and authentic happiness provide insight into the factors that contribute to individual mental well-being. On the other hand, Sufism, as a spiritual branch of Islam, offers a unique perspective on well-being through concepts such as zuhud (purification of the soul), ma'rifatullah (self-recognition of God), qalbun salim, patience and gratitude. Several studies have explored the relationship between psychology and spiritual and religious aspects. In general, it is found that individuals with higher levels of religiosity and spirituality tend to have better mental well-being. Psychology provides a scientific framework and practical techniques, while Sufism offers spiritual insights and a deep look into human nature and the purpose of life. By integrating the understanding of these two fields, it is hoped that good and reliable research results can be obtained.